Reverse martensitic transformation in the Cu-10 wt% Al-6 wt%Ag alloy - Adorno, A. T.; Silva, RAG (Springer, 2005)
The reverse martensitic transformation in the Cu-10 wt%Al-6 wt%Ag alloy was studied by classical differential thermal analysis (IDTA), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX) and X-ray diffractometry (XRD). The results indicated that the presence of Ag in the Cu-10%Al alloy is responsible for the separation of the competitive reactions that occur during the reverse martensitic transformation and is also associated to an increase in the disordering degree at high temperatures, when compared with alloys without Ag addition. (c) 2005 Springer Science + Business Media, Inc.